Coral Larvae Every Day: Leptastrea purpurea, a Brooding Species That Could Accelerate Coral Research - Nietzer, Samuel; Moeller, Mareen; Kitamura, Makoto; Schupp, Peter J. (Frontiers in Marine Science, 2018)
Sexually produced larvae are used in various fields of coral research. Because the vast majority of scleractinians reproduces only on one or few occasions per year through simultaneous release of gametes, and because an ex situ spawning induction is still very hard to achieve, great efforts are required to obtain planula larvae. Brooding corals have been used to harvest planulae although their larvae often differ in various traits from most spawning corals, e.g., in settlement behavior. Other cnidarians, such as Aiptasia spp., have been substituting for scleractinians in many aspects of coral research. However, organisms such as Aiptasia differ strongly from scleractinians, thus limiting the transferability of obtained results. This study examines the potential of Leptastrea purpurea as a reliable source of larvae for coral research. Larval output as well as settlement behavior of planulae was investigated. Our results show that colonies of L. purpurea released a daily average of 3.7 (±0.2) larvae during a period of 65 days, thus allowing continual access to planula larvae. We collected a total of 58127 larvae from our broodstock of 243 colonies. Larval settlement is induced by the same and/or similar cues as in many spawning species which increases the transferability of conclusions. We discuss the utility of L. purpurea for research on scleractinian physiology, ecology and larval settlement and conclude that L. purpurea is a well-suited organism to accelerate progress in many fields of coral research.